Post-translational modifications as key regulators of TNF-induced necroptosis - Liu, X (Cell Death Dis, 2016)
Necroptosis is a novel form of programmed cell death that is independent of caspase activity. Different stimuli can trigger necroptosis. At present, the most informative studies about necroptosis derive from the tumor necrosis factor (TNF)-triggered system. The initiation of TNF-induced necroptosis requires the kinase activity of receptor-interacting protein 1 and 3 (RIP1 and RIP3). Evidence now reveals that the ability of RIP1 and RIP3 to modulate this key cellular event is tightly controlled by post-translational modifications, including ubiquitination, phosphorylation, caspase 8-mediated cleavage and GlcNAcylation. These regulatory events coordinately determine whether a cell will survive or die by apoptosis or necroptosis. In this review, we highlight recent advances in the study of post-translational modifications during TNF-induced necroptosis and discuss how these modifications regulate the complex and delicate control of programmed necrosis.